Inequality: Measurement, Trends, Impacts and Policies. (3rd November 2017) - Addison, Tony; Pirttilä, Jukka; Tarp, Finn
Abstract : Many low‐ and middle‐income countries are achieving good rates of economic growth, while high inequality remains a priority concern. Some countries meanwhile have low growth, high inequality, and pervasive poverty—often linked to their fragility. There is now active debate on how countries should set themselves goals for achieving both absolute poverty reduction and lower inequality. But policy action needs to be better served by analysis and data.